The Impact of Socio Economic Factors on the Adherence of Patients with Gestational Diabetes Mellitus to Medical Recommendations - Ali Akbar HAGHDOOST; Mohammad Reza BANESHI; Alireza RAZZAGHI; Adel NOORI (Tehran University of Medical Sciences, 2019)
Background: Adherence to medical recommendations is very important to control gestational diabetes mellitus (GDM), as one of the most important disorders during pregnancy. In this study, we explored the impact of socio-economic status (SES) on the adherence of a cohort of GDM in Iran. Methods: In this prospective study, 230 pregnant women with confirmed GDM were followed from Feb to Jun 2013 in a referral diabetic care center in Iran. The SES of subjects were quantified using a combined score generated by principal component analysis (PSA). Medical adherence score of subjects was measured in three follow up visits in a range of 0 to 10 and were linked to SES using linear regression model. Results: The adherence scores women in the first, second, and third follow up visits were 5.06±2.12, 5.46±2.06, and 5.08±1, respectively. Women fourth quartile of SES (the highest level of SES) has a least compliance to medical orders in comparison to first quartile of SES (the lowest level of SES) with the OR -2.75 (95% Cl: -3.17, -2.23). Conclusion: The medical adherence of pregnant women with GDM is significantly poorer in high SES groups. Therefore, as an important determinant, we may target high SES pregnant women to control the adverse effects of the disorder more efficiently.